Knowledge, attitudes, and practices of community pharmacists in Manila on substandard and falsified medicines - Balugay, Keziah P.; Catapang, Christine Joy N.
The World Health Organization (WHO) recognized counterfeit drugs as a developing issue that creates a negative impact on each individual, as these cause failure to treat disease and conditions. loss of confidence in the healthcare system, and additional costs to the national health system. The term "substandard and falsified (SF) medicines" was coined during the Seventieth World Health Assembly in 2017. Substandard medicines are defined as authorized medicines failing to meet either the quality standards or specifications, while falsified medicines deliberately or fraudulently misrepresent the medicine's identity. composition, or source. This study aimed to assess the knowledge, attitudes, and practices of community pharmacists in Manila in detecting, preventing. and reporting substandard and falsified medicines. The study employed a quantitative, cross-sectional research design. A survey questionnaire was used to gather data from the selected community pharmacists. Knowledge of the community pharmacists was assessed into general concepts about SF medicines and detecting authentic drugs. The average scores of the respondents were 8.67 (SD = 1.19) and 3.85 (SD = 1.66), respectively. On the attitude, the overall mean score was 3.65 (SD = 0.27). The overall mean score for practices was 3.63 (SD : 0.25). Relationships between knowledge, attitude, practices, and sociodemographic characteristics were described using multiple linear regression. Only age (p - 0.030) and number of working hours (p - 0.046) affect attitude. Additionally, attending seminars and/or training about SF medicines affects practices (p - 0.034). Even though there was no significant relationship between the knowledge, attitude, and practices of the community pharmacists, sufficient findings on the sociodemographic factors, and attitudes and practices, implore more seminars and/or training to be conducted with the goal of more attendees, and enough working hours (8 hours per day) for the community pharmacists should be followed.